Berberine loaded liquid crystalline nanostructure inhibits cancer progression in adenocarcinomic human alveolar basal epithelial cells in vitro. Issue 11 (5th October 2021) - Mehta, Meenu; Malyla, Vamshikrishna; Paudel, Keshav R.; Chellappan, Dinesh Kumar; Hansbro, Philip M.; Oliver, Brian G.; Dua, Kamal
Abstract: Metastasis represents the leading cause of death in lung cancer patients. C‐X‐C Motif Chemokine Ligand 8 (CXCL‐8), Chemokine (C‐C motif) ligand 20 (CCL‐20) and heme oxygenase −1 (HO‐1) play an important role in cancer cell proliferation and migration. Berberine is an isoquinoline alkaloid isolated from several herbs in the Papaveraceae family that exhibits anti‐inflammatory, anticancer and antidiabetic properties. Therefore, the aim of present study is to investigate the inhibitory potential of berberine monoolein loaded liquid crystalline nanoparticles (berberine‐LCNs) against cancer progression. Berberine‐LCNs were prepared by mixing berberine, monoolein and poloxamer 407 (P407) using ultrasonication method. A549 cells were treated with or without 5 µM dose of berberine LCNs for 24 hr and total cellular protein was extracted and further analyzed for the protein expression of CCl‐20, CXCL‐8 and HO‐1 using human oncology array kit. Our results showed that berberine‐LCNs significantly reduced the expression of CCl‐20, CXCL‐8 and HO‐1 at dose of 5µM. Collectively, our findings suggest that berberine‐LCNs have inhibitory effect on inflammation/oxidative stress related cytokines i.e. CCL20, CXCL‐8, and HO‐1 which could be a novel therapeutic target for the management of lung cancer. Practical applications: Berberine is an isoquinoline alkaloid extracted from various plants of Papaveraceae family. CXCL‐8, CCL‐20 and HO‐1 play an important role in cancer progression. Our study showed that Berberine LCNs significantly downregulate the expression of CXCL‐8, CCL‐20 and HO‐1 which suggests that Berberine loaded nanoparticles could be a promising therapeutic alternative for the management of lung cancer. Abstract :